The Integration of Generative AI in Foreign Language Teacher Education: A Systematic Literature Review - Kildė, Laura (Pedagogika, 2024)
The current paper presents a systematic review that was conducted based on the Preferred Reporting Items for Systematic Reviews (PRISMA) and contains a selection of 12 articles published in the Web of Science and Scopus. The aim is to identify research trends and directions that would contribute to the body of knowledge about empirical research on GAI integration in foreign language instruction from November 2022 (the launch of OpenAi’s ChatGPT) to February 2024. The paper analyses the most novel practices, reveals teachers’ approaches, and evaluates opportunities and challenges.